2022
DOI: 10.1061/jtepbs.0000630
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of COVID-19 Pandemic on Travel Behavior in Large Cities of China: Investigation on the Lockdown and Reopening Phases

Abstract: The COVID-19 pandemic has caused worldwide lockdowns and similar containment measures aiming to curb the spread of the virus. Lockdown measures have been implemented in cities amid the COVID-19 outbreak. After the pandemic is under control, cities will be gradually reopened. This study aims to investigate the variations in urban travel behavior during the lockdown and reopening phases. On the basis of long-term traffic congestion index data and subway ridership data in eight typical cities of China, this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…However, scientists still lack sufficiently detailed data on how population mobility is evolving after the pandemic and whether (and if so, how) the criteria for choosing modes of public transport will change. While there are studies addressing this phenomenon [85][86][87], it is difficult to clearly indicate how universal their results are and to what extent they only show changes typical of the society these authors analysed. For this reason, the quantitative picture presented above requires the research to be expanded with information portraying post-pandemic mobility in Łódź in qualitative terms.…”
Section: Public Transport Provision and Its Uptakementioning
confidence: 98%
“…However, scientists still lack sufficiently detailed data on how population mobility is evolving after the pandemic and whether (and if so, how) the criteria for choosing modes of public transport will change. While there are studies addressing this phenomenon [85][86][87], it is difficult to clearly indicate how universal their results are and to what extent they only show changes typical of the society these authors analysed. For this reason, the quantitative picture presented above requires the research to be expanded with information portraying post-pandemic mobility in Łódź in qualitative terms.…”
Section: Public Transport Provision and Its Uptakementioning
confidence: 98%
“…Liu et al have discussed the effective information publishing strategy in the return to work (RTW) stage and have quantified the impact of information publishing on different types of travel demand. They found the phenomenon that private car travel demand recovered faster than public transportation travel demand when the urban transport system was fully opened to the public after the COVID-19 pandemic [183].…”
Section: The Impact Of Global Traffic Information On Day-to-day Trave...mentioning
confidence: 99%
“…By contrast, some studies have highlighted metro use responses to the recovery from post-COVID-19 or the relaxation of mobility controls. Some have found that metro ridership declines rapidly during the restriction period (to 50%–80% of pre-pandemic levels) but rebounds slowly in the return-to-work period (reaching up to 80%–90%), while car travel reaches 90%–100% of its pre-pandemic levels ( Liu et al, 2022 ). There is a potential trend of modal shift from metro transit to private car and ride-hailing at the recovery stage, as found in surveys conducted in the cities of Canada, China, and the U. S. ( Liu et al, 2022 ; Meredith-Karam et al, 2021 ; Parker et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%